A dual-mode NADH biosensor based on gold nanostars decorated CoFe₂ metal–organic frameworks to reveal dynamics of cell metabolism - Zhao, Xiaoping (2022)
Nicotinamide adenine dinucleotide (NADH) is central to metabolism and implicated in various diseases. Herein, nanohybrids of gold nanostars and metal-organic frameworks are devised and demonstrated as a dual-mode NADH sensor, for which colorimetric detection is enabled by its peroxidase-like nanozyme property and Raman detection is realized by its surface-enhanced Raman scattering property with the detection limit as low as 28 pM. More importantly, this probe enables real-time SERS monitoring in living cells, providing a unique tool to investigate dynamic cellular processes involving NADH. Our experiments reveal that metabolism dynamics is accelerated by glucose and is much higher in cancerous cells. The SERS results can also be verified by the colorimetric detection. This sensor provides a new potential to detect biomarkers and their dynamics in situ.